Interaction and Symbolism in Health Care Systems - Cersosimo, Giuseppina (Italian Sociological Review, 2019)
The purpose of this paper is to verify how and how much, interaction and symbolisms give sense and meaning to conversations and contribute to interpreting relations between patients and health professionals. They also express cultural biases, verbal and non-verbal skills, attitudes, behaviours and lifestyles. If interpreted correctly, interaction and symbolisms can optimise care relationships. Thus, symbols will be treated as factors that can help understand interaction in health care as well as its dynamics, often unintentional and predictable, that are culturally mediated. In this instance, we need to underline the growing importance of sociocultural changes in health care, (both their direct and indirect effects), as symbolic functional forms of knowledge and health literacy as well as their ability to explain systematic, though variable, relations between social statuses and healthy interaction. This paper aims to present Symbolic Interactionism as a theoretical perspective for multiple method designs with the aim of expanding the dialogue about new methodologies to manage health literacy. In other words, Symbolic Interactionism can serve as a theoretical perspective for conceptually clear and soundly implemented multiple method research, that will expand the understanding of a human’s behaviour regarding their health and their own health literacy.